Factors Affecting Teachers’ Usage of Augmented Reality in Arabic Language to Non-Native Speakers Classroom - Almelhes, Sultan; Alharbi, Abdulah; Almailabi, Bandar (Dirasat: Human and Social Sciences, 2025)
Objectives: Augmented reality is changing the service sectors, but there is paucity of research on its adoption in the education sector especially for Arabic language to non-native speakers institutes. Moreover, the adoption of augmented reality by teachers teaching Arabic to non-native speakers can help in improving the language learning. Therefore, this research aimed to examine the factors that affect the behavior intention of teachers towards augmented reality and actual use behavior of augmented reality. It could be the most appropriate model to predict technology adoption. Methods: The questionnaire was designed for data collection, and measurements were adapted from previous valid studies. The data were gathered from 63 Arabic language teachers, and Smart pls was used for analysis. Results: The results highlighted that among all elements of UTAUT including social influence (SI), effort expectancy, facilitating condition, performance expectancy, only social influence and FC influence the behavioral intention of teachers towards augmented reality and this behavioral intention leads to actual use behavior of augmented reality by teachers teaching Arabic to non-native speakers. Conclusions: The study has focused on UTAUT framework to investigate the factors affecting adoption of augmented reality among teachers teaching Arabic to non-native speakers. Teachers’ behavioral intention and usage of augmented reality in classrooms can be influenced by social influence and facilitating conditions. This research can help educational policymakers to emphasize social influence and FC to enhance behavioral intention and actual use behavior of augmented reality.